Aceitação e uso de ambiente virtual de aprendizagem no contexto de um curso de capacitação para servidores públicos - Oliveira, Bruna Miyuki Kasuya de (2011)
This study aimed to examine how students perceives the factors that may influence them to attend a training course offered in the distance virtual learning environment (VLE) of the National School of Public Administration (ENAP). Thus, as theoretical basis it was used the Unified Theory of Acceptance and Use of Technology (UTAUT), the result of an integration of eight previous models which aimed to explain the same phenomenon (acceptance/use of information technology). The research approach was a quantitative and qualitative. To achieve the study objectives were made five semi-structured interviews and an online questionnaire (websurvey) in a valid sample of 101 public employees scattered throughout the country. The technique used to the analysis of quantitative data was the structural equation modeling (SEM), by the method of Partial Least Square Path Modeling (PLS-PM). To qualitative data was the thematic content analysis. Among the results, it was found that, in the context of public service, the degree whose the individual believes that the use of an AVA will help its performance at work (performance expectancy) is a factor to its intended use and also influence its use. Among the results, it was found that the belief which the public employee has in the use of a VLE as a way to improve the performance of his work (performance expectation) was determinant for its intended use that, in turn, influenced their use. It was confirmed that, under the voluntary use of technology, the general opinion of the student s social circle (social influence) has no effect on their intention to use the VLE. The effort expectancy and facilitating conditions were not directly related to the intended use and use, respectively. However, emerged from the students speeches that the opinions of their coworkers, the ease of manipulate the VLE, the flexibility of time and place of the distance learning program and the presence of a tutor are important to their intentions to do a distance learning program. With the results, it is expected that the managers of the distance learning program of ENAP turn their efforts to reduce the impact of the causes of non-use by those unwilling to adopt voluntarily the e-learning, and enhance the potentialities of distance learning for those who are already users